2007
DOI: 10.1111/j.1742-4658.2007.06048.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of altered aspartyl residues in erythrocyte proteins from patients with Down's syndrome

Abstract: Spontaneous protein deamidation of labile Asn residues, generating l-isoaspartates and d-aspartates, is associated with cell aging and is enhanced by an oxidative microenvironment; to minimize the damage, the isoaspartate residues can be 'repaired' by a specific l-isoaspartate (d-aspartate) protein O-methyltransferase (PIMT). As both premature aging and chronic oxidative stress are typical features of Down's syndrome (DS), we tested the hypothesis that deamidated proteins may build up in trisomic patients. Blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 55 publications
0
33
0
Order By: Relevance
“…In this respect, it has been previously shown that a) human erythrocytes treated with either t -BHP or H 2 O 2 accumulate deamidated isomerized proteins in the cell membrane, which are methyl esterified ex vivo by PCMT [31]; b) human erythrocytes from G6PD-deficient subjects are particularly prone to undergo deamidation at membrane protein level, upon oxidative stress, compared to normal red cells [9]; c) melanoma cells also accumulate PCMT substrates upon UV irradiation, according to a mechanism which is mediated by an oxidation [12]. Finally, we detected increased isoaspartyl formation in the erythrocytes from patients with Down Syndrome, a condition which is characterized by increased oxidative stress [32].…”
Section: Discussionmentioning
confidence: 70%
“…In this respect, it has been previously shown that a) human erythrocytes treated with either t -BHP or H 2 O 2 accumulate deamidated isomerized proteins in the cell membrane, which are methyl esterified ex vivo by PCMT [31]; b) human erythrocytes from G6PD-deficient subjects are particularly prone to undergo deamidation at membrane protein level, upon oxidative stress, compared to normal red cells [9]; c) melanoma cells also accumulate PCMT substrates upon UV irradiation, according to a mechanism which is mediated by an oxidation [12]. Finally, we detected increased isoaspartyl formation in the erythrocytes from patients with Down Syndrome, a condition which is characterized by increased oxidative stress [32].…”
Section: Discussionmentioning
confidence: 70%
“…A previous study showed a lower concentration of plasma Hcy and SAH levels in DS children than in plasma of control subjects [11]. Galletti et al also demonstrated that the intracellular concentration of SAH is significantly reduced in DS erythrocytes, paralleling the low plasma Hcy levels, and the intracellular SAM concentration is the same as in the control cells [13]. Therefore the diminution of SAH levels could be due to other genes located on chromosome 21.…”
Section: Discussionmentioning
confidence: 94%
“…As increased expression of DYRK1A and low plasma Hcy levels have been associated with DS [6], [11][13], we also analyzed the contribution of DYRK1A on Hcy levels in a mouse trisomic complex, the Ts65Dn mice. We found an increased expression of DYRK1A in liver and a decreased level of plasma Hcy level in Ts65Dn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Down syndrome (DS) is a human genetic disease due to trisomy of chromosome 21, and it is characterized by an elevated oxidative stress status [1][2][3][4][5][6][7] as demonstrated by increase in lipid peroxidation [8], protein deamidation [9] and DNA oxidation [5,10,11]. Although the source of the oxidative stress found in DS individuals has not been fully elucidated, there is sufficient evidence indicating that it is due to an imbalance in the metabolism of reactive oxygen species (ROS).…”
Section: Introductionmentioning
confidence: 99%